The Effects of Tourism on Traditional Craftsmanship for The Sustainable Development of Historic Environments - Karakul, Özlem (European Journal of Sustainable Development, 2019)
Improving the quality of life and creating various economic benefits, conservation of cultural heritage can contribute to sustainable development as a concept having environmental, economic and socio-cultural aspects. Intangible cultural heritage as the chief reason of cultural diversity particularly guarantee sustainable development. In recent years, the increase in the concern about local ways of life, festivities, has motivated the conservation of intangible cultural heritage specifically, and contributed to the continuity of the implementation of traditional craftsmanship as a domain of intangible cultural heritage and guaranteed the sustainable development. The conservation of traditional craftsmanship necessitates providing the transmission of knowledge between master and apprentice and the continuity of practice. Through 20th century, rapidly changing life conditions, the demand for traditional craftsmanship has noticeably decreased causing the decrease in the number of practitioner craftsmen. It needs to regenerate the organic relationships of crafts with the changing life conditions for their conservation. Tourism can be a motivating force to regenerate interrelations with the increasing demand of tourists for traditional crafts. This paper aims to present the effects of tourism on crafts and discuss specific conservation approach focusing on the sustainable development of historic environments particularly focusing on 17 sustainable development goals highlighted within the 2030 Agenda for Sustainable Development published by United Nations General Assembly in 2015. Keywords: Traditional craftsmanship, tourism, conservation, historic environments, sustainable development